2019
DOI: 10.1364/ome.380601
|View full text |Cite
|
Sign up to set email alerts
|

Phonon effects in quantum dot single-photon sources

Abstract: Semiconductor quantum dots are inevitably coupled to the vibrational modes of their host lattice. This interaction reduces the efficiency and the indistinguishability of singlephotons emitted from semiconductor quantum dots. While the adverse effects of phonons can be significantly reduced by embedding the quantum dot in a photonic cavity, phonon-induced signatures in the emitted photons cannot be completely suppressed and constitute a fundamental limit to the ultimate performance of single-photon sources base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 85 publications
0
48
0
Order By: Relevance
“…where n B (ν) = [e −ν/(k B T ) − 1] −1 is the Bose distribution and μ together with the overall electron-phonon coupling α quantifies the strength of the virtual scattering process. For a typical GaAs quantum dot, we find μ = 0.023 ps 2 [47], which together with α = 0.025 ps 2 and ξ = 2.2 ps −1 correspond to γ * (4 K) = 6.7×10 −6 ps −1 and γ * (150 K) = 0.08 ps −1 .…”
Section: Appendix B: Temperature-dependent Pure Dephasingmentioning
confidence: 71%
“…where n B (ν) = [e −ν/(k B T ) − 1] −1 is the Bose distribution and μ together with the overall electron-phonon coupling α quantifies the strength of the virtual scattering process. For a typical GaAs quantum dot, we find μ = 0.023 ps 2 [47], which together with α = 0.025 ps 2 and ξ = 2.2 ps −1 correspond to γ * (4 K) = 6.7×10 −6 ps −1 and γ * (150 K) = 0.08 ps −1 .…”
Section: Appendix B: Temperature-dependent Pure Dephasingmentioning
confidence: 71%
“…While our simulations identify geometrical parameters leading to predicted performance significantly beyond state-of-the-art, the exact performance obtained experimentally will depend on unknown experimental parameters. Even though the exciton-phonon coupling strength α and the cutoff frequency ν c are QD-dependent, previous investigations have revealed that the optimum cavity linewidth for maximum indistinguishability is independent of the QD size in the 10-40 nm range 41 . Futhermore, the magnitude of the Markovian noise term as well as the unavoidable fabrication imperfections influence the performance.…”
Section: Discussionmentioning
confidence: 99%
“…with α being exciton-phonon coupling strength and ν c = √ 2v c /L denoting the cutoff frequency 40 , where v c and L are the speed of sound and the size of the QD, respectively. Here, the exciton-phonon coupling strength α depends on the QD material and on the cutoff frequency ν c , which itself is related to the size of the QD 41 . The Franck-Condon factor, B 2 , can be written compactly in terms of this function as B 2 = e −ϕ(0) .…”
Section: Master Equationmentioning
confidence: 99%
“…The model we consider in this paper consists of a localized exciton state |X that couples with a cavity mode with annihilation (creation) operator a (a † ) through the Jaynes-Cummings model [32,43]:…”
Section: Modelmentioning
confidence: 99%
“…The polariton-polaron approach is found to be the most accurate method in the strong-coupling regime, where phonons manifest themselves as sidebands on the polariton peaks [14,15]. The variational approach is, on the other hand, found to be precise in the Purcell regime, where the zero-phonon line acquires a phonon sideband [2,43].…”
Section: Introductionmentioning
confidence: 99%